Atherogenic ω-6 Lipids Modulate PPAR- EGR-1 Crosstalk in Vascular Cells. (26th October 2011) - Fei, Jia; Cook, Carla; Gillespie, Miriah; Yu, Bangning; Fullen, Khyra; Santanam, Nalini
Abstract : Atherogenic ω -6 lipids are physiological ligands of peroxisome proliferator-activated receptors (PPARs) and elicit pro- and antiatherogenic responses in vascular cells. The objective of this study was to investigate if ω -6 lipids modulated the early growth response-1 (Egr-1)/PPAR crosstalk thereby altering vascular function. Rat aortic smooth muscle cells (RASMCs) were exposed to ω -6 lipids, linoleic acid (LA), or its oxidized form, 13-HPODE (OxLA) in the presence or absence of a PPAR α antagonist (MK886) or PPAR γ antagonist (GW9662) or PPAR-specific siRNA. Our results demonstrate that ω -6 lipids, induced Egr-1 and monocyte chemotactic protein-1 (MCP-1) mRNA and protein levels at the acute phase (1–4 hrs) when PPAR α was downregulated and at subacute phase (4–12 hrs) by modulating PPAR γ, thus resulting in altered monocyte adhesion to RASMCs. We provide novel insights into the mechanism of action of ω -6 lipids on Egr-1/PPAR interactions in vascular cells and their potential in altering vascular function.